The Lancet Infectious Diseases Commission on antimicrobial resistance: 6 years later. Issue 4 (April 2020) - Laxminarayan, Ramanan; Van Boeckel, Thomas; Frost, Isabel; Kariuki, Samuel; Khan, Ejaz Ahmed; Limmathurotsakul, Direk; Larsson, D G Joakim; Levy-Hara, Gabriel; Mendelson, Marc; Outterson, Kevin; Peacock, Sharon J; Zhu, Yong-Guan
Summary: In 2013, a Lancet Infectious Diseases Commission described the state of antimicrobial resistance worldwide. Since then, greater awareness of the public health ramifications of antimicrobial resistance has led to national actions and global initiatives, including a resolution at the high-level meeting of the UN General Assembly in 2016. Progress in addressing this issue has ranged from a ban on irrational drug combinations in India to commitments to ban colistin as a growth promoter in animals, improve hospital infection control, and implement better antimicrobial stewardship. Funds have been mobilised, and regulatory barriers to new antibiotic development have been relaxed. These efforts have been episodic and uneven across countries, however. Sustained funding for antimicrobial resistance and globally harmonised targets to monitor progress are still urgently needed. Except for in a few leading countries, antimicrobial resistance has not captured the sustained focus of national leaders and country-level actors, including care providers.